THE EFFECT OF DIGITAL MARKETING STRATEGY AND BRAND AWARENESS ON CONSUMER PURCHASE DECISIONS AT BUTIK GUMUYU - Muhammad Ramdhan (BAIK Publishers, 2026)
This study aims to analyze the effect of digital marketing strategy and brand awareness on consumer purchase decisions. The research employs a quantitative approach using simple and multiple linear regression analyses to examine both partial and simultaneous effects of the independent variables on the dependent variable. The results show that digital marketing strategy has a strong, positive, and statistically significant effect on consumer purchase decisions, with a coefficient of determination of 60.9%. Brand awareness also has a positive and statistically significant effect on consumer purchase decisions, contributing 37.3% to the variance. Simultaneously, digital marketing strategy and brand awareness significantly influence consumer purchase decisions, explaining 60.9% of the total variance. These findings indicate that digital marketing strategy and brand awareness play important roles in influencing consumer purchase decisions. Companies are therefore encouraged to integrate effective digital marketing activities with strong brand-building efforts to enhance purchasing outcomes.